Development of top key performance indicators for enhancing hse commitment in selected companies / Torabi Mohammad Saeed - Torabi, Mohammad Saeed (2016)

(untitled)
Enhancing awareness regarding health, safety, and environmental (HSE) matters would alone not enforce managers to follow HSE requirements in practice. The HSE culture in business is constructed based on the outcomes of practices in the short term. In fact, managing HSE performances in the short term would shape HSE culture in the long term. A proper safety performance indicator is a basic management tool for manager decisions. Managers need the right information at the right time, which means they require reliable, relevant, sufficient, and effective data. Time is a hidden layer, extended in line with all business activities, decision making and performance assessment. This HSE performance measurement network should be developed among all managers in both static and dynamic concepts. No matter what kind of HSE management system is being implemented in a company, network communication in static concept requires each manager to have the right indicators for oneself at the right time. In a dynamic concept, this network should have the right Key Performance Indicator (KPI) to compile operational indicators into strategic drivers. On the other hand, the time period for data collection in a static concept should be adjusted within one timeline without overlapping or missing data. Blue time (BT) is the adjusted time (period of reporting) over a timeline that was developed by the author. This research was conducted on an industrial scale, by interviewing 108 managers from different organizational levels. The managers were all from Iran and Malaysian companies. Managers were asked to select 5 of 45 HSE indicators presented to them, PI while they shared the favored time for performance data gathering and HSE data reporting. The following three objectives were explored: 1) empirical investigating the top five HSE performance indicators, 2) developing BT after time investigation for performance reporting, and 3) investigating the top HSE KPIs. Three complementary iii studies were carried out to address two specifications of HSE communication in the network and to clarify the social benefit of the explored top HSE KPIs. For the dynamic concept, total hazard potential (THP) was found as the top HSE KPI, which was a risk based indicator. THP is calculated based on the safety barriers, unsafe act (UA) and unsafe conditions (UC). Iranian Companies have primarily developed this KPI. BT is the optimized time period for data collection by each management level at the dynamic concept. Contrary to the main objectives, the complementary objectives highlighted that there were significant differences among managers with different point of views. Other complementary studies, through statistical tests, clarified that a manager could not repackage the collected performance HSE reports (input data) and send these out directly. As there are no previous exploratory study on this them, the methodology of this research was exploratory with spiral approaches. This means that, after collecting data at each stage, the next stage proceeded by applying new filtering controls. The HSE communication network for the dynamic concept was constructed based on primary data in the statistical concept. Finally, the impacts of the findings were studied.